Knowledge, Attitude and Practice towards the Appropriate Use of Anti-Acne Products amongst Youths and Adults - Shamsul Anuar, Nur Qamarina; Muhammad Syawal; Muhammad Izatul Ammar; Muhammad Faiz; Melissa Izzati; Nurfarah Wahidah; Leng Xiao Qian; Shandhiyaa; Zahra Aisha Hafizah; Elida Zairina (Universitas Airlangga, 2023)
Acne is the most common skin disorder, especially in youths and adults, regardless of gender. However, with the wide range of ages and education, people's knowledge, attitudes, and practices might be diverse. Therefore, it is essential to understand the correct treatment. This study aimed to identify the knowledge, attitude, and practice towards the appropriate use of anti-acne in the community. The study was carried out in the neighbouring area of Universitas Airlangga, Surabaya, using a validated questionnaire. The data were analyzed with nonparametric correlation using Spearman Correlation. According to the data collected from 103 participants, about 62.1 % (n=64) had a moderate level of knowledge, 50.5 % had a positive attitude toward using anti-acne products, and 61.2 % (n=63) had positive responses in the practice of using anti-acne products. There was a positive correlation between the participant's knowledge and practice (p<0.001; r= 0.388). This study concludes that a health promotion program is a warranty to increase the public's level of knowledge.